Effects of supplementing narasin to Bos indicus heifers during late-gestation and lactation on development of the offspring - Miranda, Victor F. B [UNESP]; Cooke, Reinaldo F; Lasmar, Pedro V. F; Silva, Carlos E. D [UNESP]; Burato, Samir [UNESP]; Aguiar, Caio L. C [UNESP]; Ferreira, Hingryd A. O [UNESP]; Colombo, Eduardo A; Valarelli, Rodrigo L; Leiva, Tiago; Vasconcelos, Jose L. M [UNESP] (Oxford University Press (OUP), 2023)
This experiment evaluated the effects of supplementing narasin during late-gestation and lactation on productive and physiological responses of Bos indicus beef heifers and their offspring. Pregnant, nulliparous Nelore heifers (N = 88) that conceived under the same fixed-time artificial insemination protocol and to the same sire were used. Heifers were ranked by maternal ability genomic score, body weight (BW) and body condition score (BCS) and allocated to 44 drylot pens (2 heifers per pen; 10 × 25 m). Pens were ranked by these traits and alternatively assigned to receive (NAR) or not (CON) 0.260 mg of narasin/kg of heifer BW daily (Elanco Saude Animal, São Paulo, Brazil). Narasin was mixed into a supplement offered at 0.30% of heifer BW from day 0 until heifers weaned their calves (day 316), whereas CON heifers received the same supplement without narasin addition. Heifers received Urochloa brizantha hay and water for ad libitum consumption (days 0 to 316) and calved between days 97 to 112 of the experiment. After calving, heifers and offspring had access to hay and supplement; hence, supplements and narasin were offered according to heifer + calf BW beginning on day 162. No treatment differences were detected (P ≥ 0.18) for heifer BW and BCS during the experiment, although BW loss from day 0 to calving was less (P = 0.04) in NAR compared to CON heifers. Hay intake during the experiment did not differ (P = 0.79) between treatments. Serum IGF-I concentrations were greater (P = 0.05) for NAR heifers on day 60 of the experiment and did not differ (P ≥ 0.28) between treatments 24 h and 30 d after calving (treatment × day interaction; P = 0.04). No treatment effects were detected (P ≥ 0.58) for calf birth BW. Serum concentrations of total protein 24 h after birth were greater (P = 0.04) in calves from NAR compared with CON heifers, and a tendency (P = 0.10) for a similar outcome was noted for serum IgG concentrations. Diarrhea incidence did not differ (P = 0.16) between treatments, although the number of total diarrhea cases per calf were greater (P = 0.03) in the CON offspring. Growth rate of calves from NAR heifers tended (P = 0.08) to be greater, resulting in heavier calves at weaning (P ≤ 0.04) compared with CON offspring. Collectively, these outcomes indicate narasin supplementation to beef heifers as a nutritional alternative to improve cow-calf productivity via developmental programming effects during gestation, as well as direct consumption by their nursing offspring.
Keywords: beef cows; gestation; narasin; offspring; production